Inhibition of nicotinamide phosphoribosyltransferase (NAMPT), the rate-limiting enzyme of the nicotinamide adenine dinucleotide (NAD) salvage pathway, to target glioma heterogeneity through mitochondrial oxidative stress. Issue 2 (14th July 2021) - Sharma, Pratibha; Xu, Jihong; Williams, Katie; Easley, Michelle; Elder, J Brad; Lonser, Russell; Lang, Frederick F; Lapalombella, Rosa; Sampath, Deepa; Puduvalli, Vinay K
Abstract: Background: Tumor-specific metabolic processes essential for cell survival are promising targets to potentially circumvent intratumoral heterogeneity, a major resistance factor in gliomas. Tumor cells preferentially using nicotinamide phosphoribosyltransferase (NAMPT), the rate-limiting enzyme in the salvage pathway for synthesis of NAD, a critical cofactor for diverse biological processes including cellular redox reactions, energy metabolism, and biosynthesis. NAMPT is overexpressed in most malignancies, including gliomas, and can serve as a tumor-specific target. Methods: Effects of pharmacological inhibition of NAMPT on cellular oxygen consumption rate, extracellular acidification, mitochondrial respiration, cell proliferation, invasion, and survival were assessed through in vitro and ex vivo studies on genetically heterogeneous glioma cell lines, glioma stem-like cells (GSCs), and mouse and human ex vivo organotypic glioma slice culture models. Results: Pharmacological inhibition of the NAD salvage biosynthesis pathway using a highly specific inhibitor, KPT-9274, resulted in the reduction of NAD levels and related downstream metabolites, inhibited proliferation, and induced apoptosis in vitro in cell lines and ex vivo in human glioma tissue. These effects were mediated by mitochondrial dysfunction, DNA damage, and increased oxidative stress leading to apoptosis in GSCs independent of genotype, IDH status, or MGMT promoter methylation status. Conversely, NAMPT inhibition had minimal in vitro effects on normal human astrocytes (NHA) and no apparent in vivo toxicity in non-tumor-bearing mice. Conclusions: Pharmacological NAMPT inhibition by KPT9274 potently targeted genetically heterogeneous gliomas by activating mitochondrial dysfunction. Our preclinical results provide a rationale for targeting the NAMPT-dependent alternative NAD biosynthesis pathway as a novel clinical strategy against gliomas. Graphical Abstract: